Food safety for a meat derivatives plant (Revista Sistemas de Producción Agroecológicos, 2019)
All types of food products must be assured of safety, which is difficult to guarantee given that food tends to perish. To achieve a harmless final product, it must be directed to the prevention of any type of contamination that may affect it. The prerequisite programs are necessary for the implementation of a quality assurance system, these allow to guarantee compliance with the legal rules of food safety through procedures and their basic conditions that allow to control the process to which the product is subjected , raw materials, equipment and utensils, personnel and infrastructure. Processed meat products are of high risk for public health in Colombia, according to the classification given in the technical annex of Resolution 0719 of 2015. Meat is highly perishable due to its high water content, composition and pH, which favors alteration, its microbial contamination and its rapid decomposition. The type of methodology proposed for this project is descriptive and qualitative in nature since the design of the necessary prerequisites programs in the application of the food safety assurance system for a meat by-products plant was carried out, as the phases to perform: Phase 1. Preparation of the general description of the production processes of the meat derivatives plant: description of the plant, information collection (interview, checklist, and reports), preparation of the flow chart of the production processes. Phase 2. Evaluation of the hygienic and sanitary conditions of the company according to Resolution 2674 of 2013 and compliance with chapters 1: buildings and facilities and equipment and utensils, this being the starting point to meet the needs of the prerequisite programs (PPRs), to determine the mandatory aspects to intervene in each PPR. Phase 3. Apply the current regulations to each of the prerequisite programs, taking into account: review of the Colombian legislation applicable to the food industry by the Ministry of Health, National Institute of Food and Drug Surveillance (INVIMA); Ministry of Agriculture, Ministry of the Environment, Secretary of the Environment; organization of current food regulations through a matrix of legal requirements. (Includes: year, legal document, objective, complies, does not comply, pending to apply, application, task, frequency of evaluation of the legal requirement, records, responsible for the evaluation, active or repealed), for this a format was established. Phase 4. Documentation of the prerequisite programs: design of the way in which the prerequisite programs would be carried out; content of prerequisite programs (cover, header, objective, definition, legal matrix, theoretical framework, program development, Verification, attached documents, related documents); The development of the program exposes the current situation and how it is being carried out. to plan, to do, to verify and to adjust (P.D.V.A) cycle was used for the description of the program.
Keywords: meat plant; processes; quality standards